2020
DOI: 10.1002/vms3.339
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of the outbreak of subgenotype 2.5 classical swine fever virus in northern Vietnam

Abstract: Classical swine fever (CSF) is an endemic disease in southeastern Asia and is one of the most important swine diseases in Vietnam. This study was conducted to characterize the pathology of natural cases of CSF in northern Vietnam in 2018 and their genetic prevalence. A total of 10 representative pigs were collected from four provinces (Hung Yen, Ha Noi, Quang Ninh and Thai Binh) during five outbreaks and examined pathologically. The gross and histopathological findings showed the disease was expressed as the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
2
7
0
1
Order By: Relevance
“…Nowadays, CSFV strains of low and moderate virulence continue to be prevalent in some endemic countries, making the CSF control particularly difficult [ 18 , 34 ]. However, data on the viral factors that determine attenuation and persistence remain scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, CSFV strains of low and moderate virulence continue to be prevalent in some endemic countries, making the CSF control particularly difficult [ 18 , 34 ]. However, data on the viral factors that determine attenuation and persistence remain scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Even though ASFV mainly targeted the macrophages/mononuclear phagocytic system similar to both HP‐PRRSV and CSFV, the histopathological lesions in the lymph node tissues were found to be different among the viruses. There were marked histiocytic hyperplasia in CSFV infection, which is not seen in ASFV infection (Izzati et al, 2020 ). In contrast, CSFV infection manifested more marked and severe lymphoid depletion (disappearance of lymphoid follicles) compared to HP‐PRRSV infection in relation to the strain causing outbreaks in Vietnam from 2010 to 2018 (personal observation by Izzati; Huong Giang et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…phoid follicles) compared to HP-PRRSV infection in relation to the strain causing outbreaks in Vietnam from 2010 to 2018 (personal observation byIzzati;Huong Giang et al, 2016). Bacterial diseases causing similar haemorrhagic lesions, such as in septicaemic salmonellosis and swine erysipelas, were also ruled out based on negative PCR detection (data not shown) and the lack of histopathological characteristics of both bacterial infections.…”
mentioning
confidence: 99%
“…Thus far, the presence of CSFV was not quantified per intestinal layer, mucosa, submucosa, and muscular layer/serosa in infected pigs. However, the presence of CSFV was detected by immunohistochemistry (IHC) in the superficial and crypt mucosal epithelial cells of the ileum and in macrophages and lymphocytes of the Peyer’s patches [ 16 , 17 ]. Previous studies involving natural casings derived from CSFV-infected pigs have shown the presence of infectious viruses in natural casings (submucosa) after processing; however, in none of these studies, the amount of the virus was quantified [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%